Analysis of Foreign Investment Determinants in Indonesia - Nadilla Fathia; Vivi Silvia; Eddy Gunawan (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2021)
Foreign investment is an activity of investing capital from one country to another. In essence, investment is an initial step in economic development activities. Foreign investment can be influenced by several factors, such as inflation, Bank Indonesia interest rates, labor, gross domestic product, and exchange rates. From the theory and actual conditions, the researchers found a gap. From this gap, the problem in this study was how inflation, Bank Indonesia interest rates, labor, Gross Domestic Product (GDP), exchange rates, and export value affected foreign investment in Indonesia in the short and long run. The aim of this study was to determine the effect of inflation, Bank Indonesia interest rates, labor, Gross Domestic Product (GDP), exchange rates, and export value on foreign investment in Indonesia in the short run and long run. The analytical method used in this research was Autoregressive Distributed Lag (ARDL). Based on the findings, this study concludes that in the short run, the variable of inflation, Bank Indonesia interest rates, Gross Domestic Product (GDP), and exports value have significant and positive effects on foreign investment in Indonesia. Meanwhile, labor and exchange rate variables have significant and negative effects on foreign investment in Indonesia. In the long run, inflation and export value variables have significant and positive effects on foreign investment in Indonesia. In addition, interest rates of Indonesia's Bank and exchange rates have significant and negative effects on foreign investment in Indonesia. However, the variables of labor and Gross Domestic Product (GDP) have no effect on foreign investment in Indonesia.